Dynamic Imaging of LDH Inhibition in Tumors Reveals Rapid In Vivo Metabolic Rewiring and Vulnerability to Combination Therapy - Nobu Oshima; Ryo Ishida; Shun Kishimoto; Kristin Beebe; Jeffrey R. Brender; Kazutoshi Yamamoto; Daniel Urban; Ganesha Rai; Michelle S. Johnson; Gloria Benavides; Giuseppe L. Squadrito; Dan Crooks; et al. (Cell Reports, 2020)
Summary: The reliance of many cancers on aerobic glycolysis has stimulated efforts to develop lactate dehydrogenase (LDH) inhibitors. However, despite significant efforts, LDH inhibitors (LDHi) with sufficient specificity and in vivo activity to determine whether LDH is a feasible drug target are lacking. We describe an LDHi with potent, on-target, in vivo activity. Using hyperpolarized magnetic resonance spectroscopic imaging (HP-MRSI), we demonstrate in vivo LDH inhibition in two glycolytic cancer models, MIA PaCa-2 and HT29, and we correlate depth and duration of LDH inhibition with direct anti-tumor activity. HP-MRSI also reveals a metabolic rewiring that occurs in vivo within 30 min of LDH inhibition, wherein pyruvate in a tumor is redirected toward mitochondrial metabolism. Using HP-MRSI, we show that inhibition of mitochondrial complex 1 rapidly redirects tumor pyruvate toward lactate. Inhibition of both mitochondrial complex 1 and LDH suppresses metabolic plasticity, causing metabolic quiescence in vitro and tumor growth inhibition in vivo. : Oshima et al. use hyperpolarized magnetic resonance spectroscopy to dynamically monitor tumor glycolysis and oxidative phosphorylation. LDH inhibition slows tumor growth but rapidly redirects pyruvate to support mitochondrial metabolism. Inhibiting both mitochondrial complex 1 and LDH suppresses metabolic plasticity of glycolytic tumors in vivo, significantly prolonging tumor growth inhibition. Keywords: lactate dehydrogenase, pyruvate metabolism, metabolic flux, cancer, metabolic imaging, hyperpolarized magnetic resonance spectroscopic imaging